2019
DOI: 10.1021/acs.jafc.9b04614
|View full text |Cite
|
Sign up to set email alerts
|

Maltol (3-Hydroxy-2-methyl-4-pyrone) Slows d-Galactose-Induced Brain Aging Process by Damping the Nrf2/HO-1-Mediated Oxidative Stress in Mice

Abstract: Maltol, a maillard reaction product from ginseng (Panax ginseng C. A. Meyer), has been confirmed to inhibit oxidative stress in several animal models. Its beneficial effect on oxidative stress related brain aging is still unclear. In this study, the mouse model of D-galactose (D-Gal)-induced brain aging was employed to investigate the therapeutic effects and potential mechanisms of maltol. Maltol treatment significantly restored memory impairment in mice as determined by the Morris water maze tests. Long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 53 publications
(90 reference statements)
2
26
0
Order By: Relevance
“…Oxidative stress promoted cellular senescence [35]. A large number of studies have used the D-gal-induced ageing model for screening of anti-ageing compounds [26][27][28][29][32][33][34]. In our study, the D-gal-induced ageing model was well-established…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Oxidative stress promoted cellular senescence [35]. A large number of studies have used the D-gal-induced ageing model for screening of anti-ageing compounds [26][27][28][29][32][33][34]. In our study, the D-gal-induced ageing model was well-established…”
Section: Discussionmentioning
confidence: 92%
“…d-Gal can cause systematic ageing-related changes, such as hepatic and brain injury, a decline in immune function [26][27][28][29], learning and memory impairment, and fatigue in behavior studies [26,27]. Parallel histopathological features of the liver, spleen, and hippocampus were observed similarly in the d-gal-induced ageing and naturally aging groups [30].…”
Section: Discussionmentioning
confidence: 95%
“…After maintained on ice for 20 min, the samples were centrifuged at 4800 g for 20 min at 4°C. The supernatant was collected and analyzed by injection onto the chromatographic system as previously described [15].…”
Section: Determination Of Scfa Concentrationsmentioning
confidence: 99%
“…For instance, naringenin, a polyphenol, protected against OS-induced aging in a D-galactose-induced male ICR mouse model of brain aging by activating the PI3K/Akt/Nrf2 pathway and increasing the nuclear translocation of Nrf2, the expressions of HO−1, NQO1, SOD, and CAT, and the phosphorylations of PI3K and Akt (Zhang et al, 2017). A similar study showed that maltol, a Maillard reaction product of ginseng, protected against brain aging (Sha et al, 2019), activating the PI3K/Akt-mediated Nrf2/HO-1 signaling pathway. In a D-galactose-induced male ICR mouse model of brain aging, maltol inhibited cell death and suppressed the productions of OS markers (ROS and MDA) by enhancing the phosphorylations of PI3K and Akt and increasing the nuclear translocation and phosphorylation of Nrf2 and the expression of antioxidative enzymes, such as HO-1, CAT, and GSH (Sha et al, 2019).…”
Section: Non-phenolic Compoundsmentioning
confidence: 88%